Pensar y palabra: filosofía y ficción - Reguera Pérez, Isidoro (ENDOXA, 2002)
This work tries to remind a more or less forgotten Modem philosophical- historical context: a rethoric, topical and ethical one. From here we try to reconsider in the beginning of the new century the general sensitivity and making of Philosophy. We reflect upon the classical oppositions between academic and literary language, between professional and prophetic philosopher, or between pathos and logos, in general, inside Philosophy